Multi-frequency power ultrasound green extraction of polyphenols from Pingyin rose: Optimization using the response surface methodology and exploration of the underlying mechanism. (15th February 2022) - Xu, Baoguo; Feng, Min; Tiliwa, Essodézam Sylvain; Yan, Weiqiang; Wei, Benxi; Zhou, Cunshan; Ma, Haile; Wang, Bin; Chang, Lu
Abstract: The effect of multi-frequency power ultrasound (MFPU) on the extraction of Pingyin rose polyphenols (PRP) and underlying mechanisms were studied. The MFPU included mono-, dual-, and tri-frequency ultrasound. Working modes for the dual- and tri-frequency were in sequential and simultaneous ways. The extraction parameter was firstly optimized by RSM (response surface methodology). It was found that the optimum conditions were 50% for ethanol concentration, 63 °C for extraction temperature, 31 min for extraction time, and 1:46 g/mL for solid-liquid ratio with a PRP extraction yield of 156.81 mg/g. The extraction yields of PRP assisted with ultrasound in different power levels and frequencies were further investigated. Compared to non-ultrasound, the extraction yields of PRP assisted with ultrasound were significantly ( p  < 0.05) increased. The tri-frequency ultrasound in sequential working mode (20/28/40 kHz) showed the most promising extraction efficiencies for PRP (187.13 mg/g), which was 19.33% higher than that of non-ultrasound. Besides, signal results of the MFPU field collected by a hydrophone and damage degree of aluminum foil paper showed that the ultrasonic fields with stronger noise signals, and more uniform broken holes had higher extraction yield of PRP. Conclusively, the MFPU is demonstrated as a green protocol for the valuable extraction of PRP. Highlights: Effect of MFPU on extraction yield of PRP and its underlying mechanism were studied. The MFPU significantly improved the extraction yield of PRP. The MFPU in sequential mode (20/28/40 kHz) showed the most promising extraction efficiency. Ultrasonic fields with stronger noise signals and denser broken holes had higher extraction yield.